THE EFFECT OF AUDIT TENURE, COMPANY SIZE, AND AUDIT DELAY ON AUDIT QUALITY (STUDY ON NON-FINANCIAL SECTOR LISTED ON IDX FOR THE 2019-2021 PERIOD) - Eldi Januari Kristianto; Hisar Pangaribuan (JURNAL PEMBANGUNAN EKONOMI DAN KEUANGAN DAERAH, 2022)
The abstract contains a brief description (maximum 150 words) regarding the problem and research objectives, the methods used, and the research results. Abstract writing’s emphasis is mainly on research results. Abstracts are written in Indonesian and English. The abstract is typed with a single space with a narrower typing boundary than the limit of typing the main text. Therefore, keywords need to be included to describe the problem under study and the main terms that underlie the research. Keywords can be single words or a combination of words. The number of keywords is 3commentsrds. These keywords are needed for computeriztoder to facilitate the search for research titles and abstracts.